Learning Persistence Mechanisms to Become a Resilient Learner - L, Nur hikmah; Harahap, Farida (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Learning persistence among a generation of students prone to stress needs to be improved, internal factors such as self-regulated learning and external academic support are thought to influence persistence. Therefore, this study aims to examine the role of self-regulated learning as a mediator between academic support and student learning persistence. Therefore, this study aims to demonstrate the role of self-regulated learning as a mediator between academic support and student persistence. This quantitative research, conducted in South Sulawesi, Barru Regency, Tanate Riaja District, involved 213 students. The sample was determined using probability sampling. Data collection used the Perceived Academic Support Questionnaire (PASQ), Motivated Strategies for Learning Questionnaire (MSLQ), and Diligence Inventory (DI). Validity was tested using expert judgment, and reliability using Cronbach's Alpha, with reliability coefficients for the academic support scale = 0.882, self-regulated learning = 0.939, and diligence = 0.933. Data were analyzed using multiple linear regression analysis techniques in SPSS. The results showed that self-regulated learning partially mediated the relationship between academic support and persistence in high school students. The direct effect of academic support on persistence decreased from β = 0.648 (= 0.001) to β = 0.481 (p = 0.001), after the mediator variable was entered into the regression model. This finding indicates that academic support not only influences persistence directly, but also indirectly through students' self-regulated learning abilitiesKetekunan belajar pada generasi pelajar yang rentang stres perlu ditingkatkan, faktor internal seperti self- regulated learning dan eksternal academic support di anggap berpengaruh terhadap ketekunan. Oleh sebab itu penelitian ini bertujuan untuk meneliti adanya peran self-regulated learning sebagai mediator antara academic support terhadap ketekunan belajar siswa.  Penelitian ini merupakan penelitian kuantitatif dengan jenis survei. Penelitian ini dilakukan di Sulawesi Selatan. Kab. Barru. Kec. Tanate Riaja. Partisipan penelitian sebanyak 213 siswa. Penentuan sampel yaitu dengan menggunakan probability sampling. Kemudian pengumpulan data menggunakan skala Perceived Academic Support Questionnaire (PASQ), Motivated Strategie For Learning Questionnaire (MSLQ) dan Diligence inventory (DI). Uji validitas menggunakan expert judgment kemudian uji reabilitas menggunakan Cronbach’s Alpha dengan nilai koefisien reabilitas skala academic support =0,882, self-regulated learning =0,939 dan diligence 0,933. Data dianalisis menggunakan tehnik analisis regresi linear berganda menggunakan SPSS.Hasil penelitian menunjukkan bahwa self-regulated learning memediasi secara parsial hubungan antara   academic support terhadap ketekunan pada siswa SMA. Pengaruh langsung academic support terhadap ketekunan mengalami penurunan dari β =0,648 (=0,001) menjadi β=0,481 (p=0,001), setelah variabel meditor dimasukkan ke dalam model regresi. Temuan ini menunjukkan bahwa academic support tidak hanya mempegaruhi ketekunan secara langsung, tetapi juga secara tidak langsung melalui kemampuan self-regulated learning siswa.